The Effect of Principal Leadership on Improving School Quality in MAN Bintan - Nurul Fitriyana Ahmad (Program Studi Magister Manajemen Pendidikan)
Abstrak:The Effect of Principal Leadership on Improving School Quality in MAN Bintan. This study aims to determine: the effect of leadership of the principal in MAN Bintan and how the effect of principal leadership on improving school quality in MAN Bintan. This research is a quantitative study. Data collected through questionnaries and documentation. And analyzed with technical analysis of validity test, reliabitily test, prerequisite test, and simple regression test. The conclusion in this study is thate there in an effect between principal leadership to improving school quality with the result of the correlation test, it is know that there is a positive relationship between principal leadership and quality improvement with the pearson correlation coefficient of 0,916 which mean that the effect is very high. With the percentage of determination coefficient og 84%. This shows that the better the leadership of principal, the better quality of school.Keywords : Leadership, Principal and School QualityDOI: 10.23960/jmmp .v9.i1.202104